Sesame - high energy health food - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The Executive Director of the National Women Sesame Farmers' Association in The Gambia explains the nutritional and income-generating values of the crop, particularly for pregnant and breastfeeding women.